Rheokinetic Analysis of Hydroxy Terminated Polybutadiene Based Solid Propellant Slurry - Abhay K Mahanta; Monika Goyal; Devendra D Pathak (E-Journal of Chemistry)
The cure kinetics of propellant slurry based on hydroxy-terminated polybutadiene (HTPB) and toluene diisocyanate (TDI) polyurethane reaction has been studied by viscosity build up method. The viscosity (ɳ)–time (t) plots conform to the exponential function ɳ = aebt, where a & b are empirical constants. The rate constants (k) for viscosity build up at various shear rate (rpm), evaluated from the slope of dɳ/dt versus ɳ plots at different temperatures, were found to vary from 0.0032 to 0.0052 min-1. It was observed that the increasing shear rate did not have significant effect on the reaction rate constants for viscosity build up of the propellant slurry. The activation energy (Eɳ), calculated from the Arrhenius plots, was found to be 13.17±1.78 kJ mole-1, whereas the activation enthalpy (∆Hɳ*) and entropy (∆Sɳ*) of the propellant slurry, calculated from Eyring relationship, were found to be 10.48±1.78 kJ mole-1 and –258.51± 5.38 J mole-1K-1, respectively. The reaction quenching temperature of the propellant slurry was found to be -9 ° C, based upon the experimental data. This opens up an avenue for a “freeze-and-store”, then “warm-up and cast”, mode of manufacturing of very large solid rocket propellant grains.